2006
DOI: 10.3842/sigma.2006.018
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of a Generalized Chiral Quark Soliton Model

Abstract: Abstract. A generalized version of the so-called chiral quark soliton model (CQSM) in nuclear physics is introduced. The Hamiltonian of the generalized CQSM is given by a Dirac type operator with a mass term being an operator-valued function. Some mathematically rigorous results on the model are reported. The subjects included are: (i) supersymmetric structure; (ii) spectral properties; (iii) symmetry reduction; (iv) a unitarily equivalent model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…From this point of view, it would be interesting to investigate if the Hamiltonian of the present model has supersymmetry. Indeed, it was shown that the Hamiltonian of the CQS model as well as that of the GCQS model has supersymmetry [3,4]. In this section we see that a supersymmetric structure similar to that of the CQS (GCQS) model exists in our model.…”
Section: =1supporting
confidence: 54%
See 4 more Smart Citations
“…From this point of view, it would be interesting to investigate if the Hamiltonian of the present model has supersymmetry. Indeed, it was shown that the Hamiltonian of the CQS model as well as that of the GCQS model has supersymmetry [3,4]. In this section we see that a supersymmetric structure similar to that of the CQS (GCQS) model exists in our model.…”
Section: =1supporting
confidence: 54%
“…In the papers [3,4], it was shown that, under a suitable condition, the Hamiltonian of the CQS (GCQS) model is unitarily transformed to a Dirac operator which is simpler in a sense. In this section, we show that those structures are unified into a simple general structure.…”
Section: Unitary Equivalence To a Gauge Theoretic Dirac Operator And mentioning
confidence: 99%
See 3 more Smart Citations